The impact of nutrition education intervention with and without a mobile phone application on nutrition knowledge among young endurance athletes - Heikkilä, M.; Lehtovirta, M.; Autio, O.; Fogelholm, M.; Valve, R. (Nutrients, 2019)
Athletes often have significant gaps in their nutrition knowledge. Thus, the aim of this study was to investigate whether young Finnish endurance athletes` nutrition knowledge and dietary intake can be improved through an education intervention with or without a mobile food application. Seventy-nine endurance athletes, 18.0 years (SD: 1.4), participated in this randomized, controlled intervention. We compared the effects of participatory nutrition education sessions alone (group EDU) to those including the use of a mobile food application (group EDU + APP) for four days after each session. Both groups attended three 90-min education sessions fortnightly. The participants completed a validated nutrition knowledge questionnaire in Weeks 0, 5, and 17, and a three-day food diary in Weeks 0 and 17. The education plan was based on the Self-Determination Theory and the concept of meaningful learning process. The EDU group`s nutrition knowledge scores were: 78 (week 0), 85 (week 5), and 84 (week 17) and the EDU + APP group`s 78, 86, and 85, respectively. Nutrition knowledge increased significantly (main effect of time (p < 0.001)), but we observed no significant group × time interaction (p = 0.309). The changes in dietary intakes were minor (p > 0.05). The amount of carbohydrates was below endurance athletes` recommendations throughout the intervention. The reported energy intakes were also below the estimated energy expenditures. In conclusion, nutrition knowledge improved significantly after only three education sessions and food diary feedback, but the mobile app did not improve learning further. However, the nutrition education intervention alone was not enough to change dietary intake.